An integrated approach to the analysis of creep, chemical expansion, creep damage and lifetime reduction for solid oxide fuel cells - Zolochevsky, A.; Hyde, T. H.; Zhaoji, Hu (NTU "KhPI", 2007)
In this paper, a comprehensive theoretical and numerical investigation has been carried out with the main focus directed at the understanding on how electrochemical transport phenomena, diffusional creep and chemical expansion in electrochemical ceramics affect creep damage growth and lifetime reduction for Solid Oxide Fuel Cell systems. Furthermore, focus is put on how the electrochemical diffusion, creep process, chemical expansivity as well as the creep damage growth in ceramic substances may be controlled in order to reduce stack degradation below 0.1%/1,000 hours, optimize cell, stack design and operating conditions, and extend stack lifetime above 40,000 hours for stationary applications and above 5,000 hours for transportation applications.

Теоретичні та чисельні дослідження даної роботи направлено на дослідження впливу явища електрохімічного переносу, дифузійної повзучості та хімічного розпухання в електрохімічній кераміці на ріст пошкоджуваності, що обумовлена повзучістю, та зниження часу безвідмовної роботи паливних елементів на твердому оксиді. Також в роботі досліджено, як керуючи електрохімічною дифузією, процесом повзучості, хімічним розширенням та процесами пошкоджуваності в керамічних матеріалах знизити деградацію батарей нижче 0,1%/1000 годин, забезпечити оптимізацію паливних елементів, конструкції батарей та умов керування, збільшити термін роботи до 40000 годин при стаціонарному використанні та до 5000 годин при використанні в транспортних умовах.
Keywords: electrochemical transport phenomena; diffusional creep; electrochemical ceramics; electrochemical diffusion; явище електрохімічного переносу; дифузійна повзучість; електрохімічна кераміка; електрохімічна дифузія